Employability skills mastery of special needs students at polytechnics - Puteh, S.; Maisarah, M.; Rosnawati, B. (Universiti Putra Malaysia Press, 2017)
This study attempts to examine the employability skills of students with special needs. Employability skills are related to soft skills and hard skills. The respondents were 81 impaired students in four polytechnics (Politeknik Sultan Salahuddin Abdul Aziz Shah (PSA), Politeknik Ibrahim Sultan (PIS), Politeknik Ungku Omar (PUO) and Politeknik Kota Kinabalu (PKK). The aim of this study is to identify the extent of implementation and control employability skills among special needs students in polytechnics as well as to recommend improvements to the quality of TVET graduates. Data were analysed using the Statistical Package for the Social Sciences (SPSS) version 20.0 to calculate and process the descriptive and inferential statistical findings. Mean scores for all three problems were high implementation employability skills (soft skills=3.70 and hard skills=3.86). The mean score for employability skills competency mastery of special needs students in polytechnics was 3.89, while the correlation between employability skills and mastery of skills competency was 0.776 (r), showing a relationship between application of employability skills and mastery of employability skills of special need students in polytechnic. The results showed that the activities that contribute to improved employability skills of students with special needs should be intensified to help them compete in the job market and contribute to national development.